Solid polymer electrolyte membrane and preparation method thereof, solid-state battery and mechanical device
By using a combined structure of an organic framework and a polymer electrolyte in the solid-state polymer electrolyte membrane, the problem of insufficient low ionic conductivity and mechanical properties of the electrolyte membrane in the prior art is solved, and higher ionic conductivity and mechanical strength are achieved, and the electrochemical performance of the battery is improved.
Patent Information
- Application Number
- CN202411940303.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-25
AI Technical Summary
The existing solid polymer electrolyte membrane has low ionic conductivity and poor mechanical properties, resulting in poor electrochemical performance of the battery and is prone to penetration by dendrites.
An organic framework including polymers and lithium salts is used, and polymerized in their pores to form polymer electrolytes, improving the shuttle capacity and mechanical strength of lithium ions.
It significantly improves the ionic conductivity and mechanical properties of the solid polymer electrolyte membrane, reduces the risk of penetration by lithium dendrites, and improves the overall performance of the battery.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solid-state batteries, and in particular to a solid polymer electrolyte membrane and a preparation method thereof, a solid-state battery and a mechanical device. Background Art
[0002] Lithium-ion batteries have been widely used in portable electronic devices and electric vehicles, promoting sustainable energy transformation. However, the flammability and leakage of liquid electrolytes pose serious safety hazards to batteries. In addition, with the continuous development of lithium-ion batteries, their energy density has reached its limit. Therefore, it is necessary to develop a new battery system to improve the battery energy density while ensuring battery safety.
[0003] The solid electrolyte in solid-state batteries has flame retardant properties, which can greatly improve battery safety. In addition, solid-state batteries can preferably use lithium metal as the negative electrode. The high energy density of lithium metal negative electrode (3860mAh g -1 ) and low redox potential (-3.04V) can significantly increase the energy density of the battery (500Wh kg -1 ).
[0004] Solid polymer electrolyte is a type of solid electrolyte, which is widely used in solid-state batteries due to its good flexibility and good contact with electrodes. However, the low ionic conductivity and poor mechanical properties of solid polymer electrolytes make them easily penetrated by dendrites, thus greatly reducing the electrochemical performance of the battery. Summary of the invention
[0005] The present invention aims to solve one of the technical problems in the prior art at least to a certain extent. To this end, one object of the present invention is to provide a solid polymer electrolyte membrane and a preparation method thereof, a solid-state battery and a mechanical device.
[0006] In a first aspect of the present invention, the present invention provides a solid polymer electrolyte membrane. According to an embodiment of the present invention, the solid polymer electrolyte membrane comprises: An organic skeleton, wherein the organic skeleton comprises a polymer and a lithium salt, wherein the polymer comprises at least one of a polyether, a polyester and a polyolefin; A polymer electrolyte is filled in the pores of the organic skeleton. The polymer electrolyte is formed by polymerization of a polymer monomer, a lithium salt and an initiator in the pores of the organic skeleton.
[0007] According to the above-mentioned solid polymer electrolyte membrane of the present invention, it includes an organic skeleton and a polymer electrolyte, and the polymer electrolyte is filled in the pores of the organic skeleton. The organic skeleton of polyether, polyester or polyolefin is used, and the organic skeleton can provide excellent mechanical support, which enhances the rigidity and mechanical properties of the solid polymer electrolyte membrane as a whole. The organic skeleton also includes lithium salt. By adding lithium salt to the organic skeleton, the organic skeleton has a certain lithium ion conductivity, which improves the shuttle ability of lithium salt in the organic skeleton and the polymer electrolyte, thereby improving the ionic conductivity of the entire solid polymer electrolyte membrane. The polymer electrolyte is formed by polymerizing monomers, lithium salts and initiators after mixing, and the polymerization reaction occurs in the pores of the above-mentioned organic skeleton, so that the polymer monomers can be closely connected and fully fill the voids of the skeleton. The formed polymer electrolyte is a continuous phase in the organic skeleton, forming a dense integrated structure, which improves the interface compatibility between the polymer electrolyte and the organic skeleton, which is conducive to the rapid conduction of lithium ions, and on the other hand, significantly improves the mechanical strength of the solid polymer electrolyte membrane, and effectively reduces the risk of being penetrated by lithium dendrites. Thus, the solid polymer electrolyte membrane has excellent mechanical properties and high ionic conductivity.
[0008] In addition, the solid polymer electrolyte membrane according to the above embodiment of the present invention may also have the following technical features: In some embodiments of the present invention, the mass proportion of the lithium salt in the organic skeleton is 5-50%, preferably 20-50%.
[0009] In some embodiments of the present invention, the porosity of the organic framework is 20-60%.
[0010] In some embodiments of the present invention, the polyether includes at least one of polyethylene oxide and polyethylene glycol.
[0011] In some embodiments of the present invention, the polyester includes at least one of polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, polymethyl methacrylate, polyethylene glycol methyl ether methacrylate, polycarbonate, polypropylene carbonate and polypropylene carbonate.
[0012] In some embodiments of the present invention, the polyolefin includes at least one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyvinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene, polyacrylonitrile, polyethylene, polypropylene, polyvinyl chloride, polystyrene and polytetrafluoroethylene.
[0013] In some embodiments of the present invention, the mass percentage of the lithium salt in the polymer electrolyte is 5-50%, preferably 20-50%.
[0014] In some embodiments of the present invention, the polymerizable monomer includes at least one of an ether functional group and an ester functional group, and the polymerizable monomer further includes at least one of a cyano group and a fluorine group.
[0015] In some embodiments of the present invention, the polymerizable monomer includes at least one of 3-amino-4-fluorobenzoic acid allyl ester, 4-amino-3-fluorobenzoic acid allyl ester, 4-fluorocinnamic acid ethyl ester, 4-fluorocinnamic acid methyl ester, pentafluorophenyl acrylate, pentafluorobenzyl methacrylate, pentafluorophenyl methacrylate, 2-fluorophenyl allyl ether, allyl pentafluorophenyl ether and α-cyano-4-fluorocinnamic acid ethyl ester.
[0016] In some embodiments of the present invention, the mass ratio of the organic skeleton to the polymer electrolyte is (2-4): (1-3).
[0017] In some embodiments of the present invention, the thickness of the solid polymer electrolyte membrane is 30-70 μm.
[0018] In a second aspect of the present invention, the present invention provides a method for preparing the above-mentioned solid polymer electrolyte membrane. According to an embodiment of the present invention, the method comprises: (1) dissolving a polymerization monomer, a lithium salt and an initiator in a solvent to obtain a polymerization precursor mixed solution; (2) The organic skeleton is immersed in the polymer precursor mixture and then dried to obtain a solid polymer electrolyte membrane.
[0019] According to the method for preparing a solid polymer electrolyte membrane of the present invention, a polymer monomer, a lithium salt and an initiator are dissolved in a solvent to obtain a polymer precursor mixture, and then an organic skeleton is placed in the polymer precursor mixture for infiltration, and then dried. The drying provides heat, which, on the one hand, causes the polymer monomer to self-polymerize, and on the other hand, removes the second solvent to obtain a solid polymer electrolyte membrane. The above-mentioned self-polymerization reaction occurs in the pores of the organic skeleton, so that the polymer monomer can be tightly connected and fully fill the skeleton voids. The formed polymer electrolyte is a continuous phase in the organic skeleton to form a dense integrated structure. On the one hand, the interfacial compatibility between the polymer electrolyte and the organic skeleton is improved, which is conducive to the rapid conduction of lithium ions. On the other hand, the mechanical strength of the solid polymer electrolyte membrane is significantly improved, and the risk of being penetrated by lithium dendrites is effectively reduced. Therefore, the method can be used to prepare a solid polymer electrolyte membrane with excellent mechanical properties and high ionic conductivity.
[0020] In addition, the method for preparing a solid polymer electrolyte membrane according to the above embodiment of the present invention also has the following technical features: In some embodiments of the present invention, in step (2), the drying temperature is 60-100°C, preferably 60-80°C.
[0021] In some embodiments of the present invention, in step (2), the soaking time is 5 to 10 minutes and the temperature is 25°C to 30°C.
[0022] In some embodiments of the present invention, the method for preparing the organic skeleton comprises: dissolving a polymer, a lithium salt and a foaming agent in a solvent, applying the solvent and drying the solvent to obtain the organic skeleton.
[0023] In some embodiments of the present invention, the drying temperature is 60°C to 250°C, preferably 60°C to 200°C.
[0024] In some embodiments of the present invention, the foaming agent includes at least one of an azo compound, a sulfonyl hydrazide compound, a semicarbazide, a tetrazole compound, a nitroso compound and a carbonate.
[0025] In a third aspect of the present invention, the present invention provides a solid-state battery. According to an embodiment of the present invention, the solid-state battery comprises the above-mentioned solid polymer electrolyte membrane or the solid polymer electrolyte membrane prepared by the above-mentioned method. Thus, the solid-state battery has high energy density, long cycle life and reliable safety.
[0026] In a fourth aspect of the present invention, the present invention provides a mechanical device. According to an embodiment of the present invention, the mechanical device includes the above-mentioned solid-state battery. As a result, the mechanical device has a long driving range and service life. DETAILED DESCRIPTION
[0027] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.
[0028] In a first aspect of the present invention, the present invention provides a solid polymer electrolyte membrane. According to an embodiment of the present invention, the solid polymer electrolyte membrane comprises: An organic skeleton, wherein the organic skeleton comprises a polymer and a lithium salt, wherein the polymer comprises at least one of a polyether, a polyester and a polyolefin; A polymer electrolyte is filled in the pores of the organic skeleton. The polymer electrolyte is formed by polymerization of a polymer monomer, a lithium salt and an initiator in the pores of the organic skeleton.
[0029] According to the above-mentioned solid polymer electrolyte membrane of the present invention, it includes an organic skeleton and a polymer electrolyte, and the polymer electrolyte is filled in the pores of the organic skeleton. The organic skeleton of polyether, polyester or polyolefin is used, and the organic skeleton can provide excellent mechanical support, which enhances the rigidity and mechanical properties of the solid polymer electrolyte membrane as a whole. The organic skeleton also includes lithium salt. By adding lithium salt to the organic skeleton, the organic skeleton has a certain lithium ion conductivity, which improves the shuttle ability of lithium salt in the organic skeleton and the polymer electrolyte, thereby improving the ionic conductivity of the entire solid polymer electrolyte membrane. The polymer electrolyte is formed by polymerizing monomers, lithium salts and initiators after mixing, and the polymerization reaction occurs in the pores of the above-mentioned organic skeleton, so that the polymer monomers can be closely connected and fully fill the skeleton gaps. The formed polymer electrolyte is a continuous phase in the organic skeleton, forming a dense integrated structure, which improves the interface compatibility between the polymer electrolyte and the organic skeleton, which is conducive to the rapid conduction of lithium ions, and on the other hand, significantly improves the mechanical strength of the solid polymer electrolyte membrane, and effectively reduces the risk of being penetrated by lithium dendrites. Thus, the solid polymer electrolyte membrane has excellent mechanical properties and high ionic conductivity.
[0030] It should be noted that lithium salts are conventional materials in the field and can be selected by those skilled in the art. For example, lithium salts include but are not limited to at least one of LiTFSI, LiFSI, LiClO4, LiPF6, LiAsF6, LiBF4, LiPF4, LiBOB, LiFAB, LiODFB, LiDODFP, LiOTFP and LiTf.
[0031] According to an embodiment of the present invention, the mass proportion of the lithium salt in the organic skeleton is 5-50%, preferably 20-50%, for example, the mass proportion is 5%, 10%, 20%, 30%, 40%, 50%, etc., or the range between any two of the above values. Controlling the mass proportion of the lithium salt in the organic skeleton within the above range not only ensures the support strength of the organic skeleton, but also improves the ionic conductivity of the organic skeleton, and better cooperates with the lithium salt in the polymer electrolyte to play a role, thereby improving the ionic conductivity of the solid polymer electrolyte membrane.
[0032] According to an embodiment of the present invention, the porosity of the organic skeleton is 20-60%, for example, the porosity is 20%, 30%, 40%, 50%, 60%, etc., or a range between any two of the above values. The porosity of the organic skeleton is within the above range, which can ensure an appropriate amount of polymer electrolyte, ensure the ionic conductivity of the electrolyte, and improve the supporting strength of the organic skeleton, thereby improving the overall mechanical properties of the solid polymer electrolyte membrane.
[0033] According to an embodiment of the present invention, the polyether includes at least one of polyethylene oxide and polyethylene glycol.
[0034] According to an embodiment of the present invention, the polyester includes at least one of polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, polymethyl methacrylate, polyethylene glycol methyl ether methacrylate, polycarbonate, polypropylene carbonate and polypropylene carbonate.
[0035] According to an embodiment of the present invention, the polyolefin includes at least one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyvinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene, polyacrylonitrile, polyethylene, polypropylene, polyvinyl chloride, polystyrene and polytetrafluoroethylene.
[0036] According to an embodiment of the present invention, the mass proportion of the lithium salt in the polymer electrolyte is 5-50%, preferably 20-50%, for example, the mass proportion is 5%, 10%, 20%, 30%, 40%, 50%, etc., or the range between any two of the above values. Controlling the mass proportion of the lithium salt in the polymer electrolyte within the above range can improve the ionic conductivity of the polymer electrolyte and better cooperate with the lithium salt in the organic skeleton, thereby improving the ionic conductivity of the solid polymer electrolyte membrane.
[0037] According to an embodiment of the present invention, the polymerized monomer includes at least one of an ether functional group and an ester functional group, and the polymerized monomer also includes at least one of a cyano group and a fluorine group. At the same time, the polymerized monomer includes at least one of an ether functional group (CO) and an ester functional group (O=CO), and the polymerized monomer also includes at least one of a cyano group (-CN) and a fluorine group (-F). The presence of the ether functional group and the ester functional group increases the Li + The action site increases the Li + The fast transport capability can improve the ionic conductivity of the solid polymer electrolyte membrane, and the presence of fluorine and cyanide groups can form a SEI film that is stable to lithium, regulating the Li + Stripping and deposition stabilize the solid interface and reduce the formation of lithium dendrites.
[0038] Preferably, the polymerizable monomer includes at least one of 3-amino-4-fluorobenzoic acid allyl ester, 4-amino-3-fluorobenzoic acid allyl ester, 4-fluorocinnamic acid ethyl ester, 4-fluorocinnamic acid methyl ester, pentafluorophenyl acrylate, pentafluorobenzyl methacrylate, pentafluorophenyl methacrylate, 2-fluorophenyl allyl ether, allyl pentafluorophenyl ether and ethyl α-cyano-4-fluorocinnamate.
[0039] Preferably, the polymerizable monomer is at least one of 3-amino-4-fluorobenzoic acid allyl ester, 4-fluorocinnamic acid methyl ester, pentafluorobenzyl methacrylate, 2-fluorophenyl allyl ether and α-cyano-4-fluorocinnamic acid ethyl ester.
[0040] According to an embodiment of the present invention, the mass ratio of the organic skeleton and the polymer electrolyte is (2-4): (1-3), for example, the mass ratio is 2:1, 2:2, 2:3, 3:1, 3:2, 4:1, 4:3, etc., or a range between any two of the above values. Controlling the mass ratio of the organic skeleton and the polymer electrolyte within the above range is conducive to fully volatilizing the supporting effect of the organic skeleton and the ionic conductivity of the polymer electrolyte, while allowing the two to work together to maximize their effects.
[0041] According to an embodiment of the present invention, the thickness of the solid polymer electrolyte membrane is 30-70 μm. Controlling the thickness of the solid polymer electrolyte membrane within the above range can not only ensure the mechanical strength of the solid polymer electrolyte membrane, but also give full play to the ion transport performance of the electrolyte, and have excellent lithium ion conductivity, thereby ensuring the high ion conductivity and good mechanical properties of the solid polymer electrolyte membrane.
[0042] According to an embodiment of the present invention, the initiator includes but is not limited to azobisisobutyronitrile, azobisisoheptanenitrile, azobisisovaleronitrile, dimethyl azobisisobutyrate, di-tert-butyl azodicarboxylate, and diisopropyl azodicarboxylate.
[0043] In a second aspect of the present invention, the present invention provides a method for preparing the above-mentioned solid polymer electrolyte membrane. According to an embodiment of the present invention, the method comprises: S100: Dissolve the polymerization monomer, lithium salt and initiator in the solvent In this step, the polymerizable monomer, lithium salt and initiator are dissolved in a solvent to obtain a polymerizable precursor mixed liquid, in which the polymerizable monomer still exists in the form of a monomer.
[0044] It should be noted that the solvent is a conventional reagent in the art and can be selected by those skilled in the art according to actual conditions. For example, the solvent includes but is not limited to at least one of N,N-dimethylformamide, N,N-dimethylpyrrolidone, dimethyl sulfoxide, N,N-dimethylacetamide, diethyl carbonate, dimethyl carbonate and ethylene carbonate.
[0045] According to an embodiment of the present invention, the mass fraction of the polymer monomer in the polymerization precursor mixture is 10-30%, preferably 20-30%. By controlling the mass fraction of the polymer monomer in the polymerization precursor mixture within the above range, the polymerization precursor mixture can quickly infiltrate the organic skeleton and evenly and fully fill the pores of the organic skeleton.
[0046] S200: Infiltrate the organic framework into the polymer precursor mixture and then dry it In this step, the organic skeleton is immersed in the polymerization precursor mixture and then dried. The drying provides heat, which, on the one hand, causes the polymerization monomers to self-polymerize, and on the other hand, removes the second solvent to obtain a solid polymer electrolyte membrane. The above self-polymerization reaction occurs in the pores of the organic skeleton, so that the polymerization monomers can be tightly connected and fully fill the skeleton voids. The formed polymer electrolyte is a continuous phase in the organic skeleton to form a dense integrated structure. On the one hand, the interface compatibility between the polymer electrolyte and the organic skeleton is improved, which is beneficial to the rapid conduction of lithium ions. On the other hand, the mechanical strength of the solid polymer electrolyte membrane is significantly improved, and the risk of being penetrated by lithium dendrites is effectively reduced.
[0047] According to an embodiment of the present invention, the drying temperature is 60°C to 100°C, preferably 60°C to 80°C. For example, the temperature is 60°C, 70°C, 80°C, 90°C, 100°C, etc., or a range between any two of the above values. By controlling the drying temperature within the above range, it can be ensured that the polymerization monomers fully undergo self-polymerization reaction to form a continuous and dense electrolyte, and the solvent can also be fully volatilized.
[0048] According to an embodiment of the present invention, the soaking time is 5-10 min and the temperature is 25° C.-30° C. By controlling the soaking time and temperature within the above range, the polymer precursor mixture can evenly and fully fill the pores of the organic skeleton to form a composite structure supported by the organic skeleton and filled with self-polymerized electrolyte.
[0049] According to an embodiment of the present invention, the preparation method of the organic skeleton comprises: coating and drying a mixed solution obtained by dissolving a polymer, a lithium salt and a foaming agent in a solvent to obtain an organic skeleton. After dissolving a polymer, a lithium salt and a foaming agent in a solvent, coating and drying are performed, and the foaming agent is decomposed to form a three-dimensional organic skeleton rich in pores. The organic skeleton provides mechanical support and enhances the rigidity of the solid polymer electrolyte membrane. By adding a lithium salt to the organic skeleton, the ionic conductivity of the organic skeleton can be improved. Specifically, an organic skeleton with a certain porosity can be obtained by controlling the amount of the foaming agent added and the type of the foaming agent. It should be noted that the above-mentioned solvent is a conventional reagent in the art, and those skilled in the art can select it according to actual conditions. For example, the solvent includes but is not limited to at least one of N, N-dimethylformamide, N, N-dimethylpyrrolidone, dimethyl sulfoxide, N, N-dimethylacetamide, diethyl carbonate, dimethyl carbonate and ethylene carbonate.
[0050] Preferably, the foaming agent includes at least one of an azo compound, a sulfonyl hydrazide compound, a semicarbazide, a tetrazole compound, a nitroso compound and a carbonate.
[0051] By way of example, azo compounds include, but are not limited to, azodicarbonamide, diisopropyl azodicarboxylate.
[0052] As examples, sulfonyl hydrazide compounds include, but are not limited to, p-toluenesulfonyl hydrazide and 4,4'-oxybisbenzenesulfonyl hydrazide.
[0053] By way of example, semicarbazides include, but are not limited to, p-toluenesulfonyl semicarbazide.
[0054] As examples, tetrazole compounds include, but are not limited to, 5-phenyltetrazole and methyltetrazole.
[0055] By way of example, nitroso compounds include, but are not limited to, N,N'-dinitrosopentamethylenetetramine.
[0056] By way of example, carbonates include, but are not limited to, sodium bicarbonate, ammonium carbonate.
[0057] According to an embodiment of the present invention, the drying temperature is 60°C to 250°C, preferably 60°C to 200°C. For example, the temperature is 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 250°C, etc., or a range between any two of the above points. Controlling the drying temperature within the above range can ensure that the foaming agent is decomposed and discharged to form pores, while fully evaporating the solvent to obtain an organic skeleton with uniform pores. It can be understood by those skilled in the art that by controlling the type of foaming agent, the amount added and the foaming temperature (drying temperature), the porosity of the organic skeleton can be made 20 to 60%. Those skilled in the art can select the type of foaming agent, the amount added and the foaming temperature according to the required porosity.
[0058] Preferably, the mass proportion of the foaming agent in the mixed solution is 5-15%.
[0059] Therefore, the method can be used to prepare a solid polymer electrolyte membrane with excellent mechanical properties and high ionic conductivity, and the method is simple in process, low in cost, and suitable for popularization and application. It should be noted that the characteristics and advantages described above for the solid polymer electrolyte membrane are also applicable to this method, and will not be repeated here.
[0060] In the third aspect of the present invention, the present invention provides a solid-state battery. According to an embodiment of the present invention, the solid-state battery comprises the above-mentioned solid polymer electrolyte membrane or the solid polymer electrolyte membrane prepared by the above-mentioned method. As a result, the solid-state battery has high energy density, long cycle life and reliable safety. It should be noted that the features and advantages described above for the solid polymer electrolyte membrane and its preparation method are also applicable to the solid-state battery, and will not be repeated here.
[0061] According to an embodiment of the present invention, a solid-state battery includes a positive electrode sheet, a solid polymer electrolyte membrane and a negative electrode sheet.
[0062] As an example, the main material of the positive electrode plate includes but is not limited to one or more combinations of nickel-cobalt-manganese ternary materials, nickel-cobalt-aluminum ternary materials, lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, and lithium vanadium phosphate; the main material of the negative electrode plate includes but is not limited to one or more combinations of graphite, graphene, carbon nanotubes, silicon-based alloys, silicon-oxygen negative electrodes, silicon-carbon negative electrodes, lithium metal, lithium alloy negative electrodes, lithium titanium oxides, transition metal oxides, and transition metal sulfides.
[0063] In a fourth aspect of the present invention, the present invention proposes a mechanical device. According to an embodiment of the present invention, the mechanical device includes the above-mentioned solid-state battery. As a result, the mechanical device has a long driving range and service life. It should be noted that the features and advantages described above for the solid-state battery are also applicable to the mechanical device and will not be repeated here.
[0064] According to an embodiment of the present invention, the mechanical device includes but is not limited to a motorcycle, a car, a truck, a ship, etc.
[0065] The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.
[0066] Example 1 The preparation process of the solid polymer electrolyte membrane of Example 1 is as follows: (1) Polyvinylidene fluoride, LiTFSI and p-toluenesulfonyl hydrazide are dissolved in dimethyl sulfoxide. The mass proportion of p-toluenesulfonyl hydrazide in the obtained mixed solution is 15%. The mixed solution is coated on a substrate and then vacuum dried at 150°C. During the drying process, the foaming agent p-toluenesulfonyl hydrazide decomposes to form a three-dimensional organic skeleton rich in pores. The porosity of the organic skeleton is 60%. Based on the total mass of the organic skeleton, the mass proportion of LiTFSI is 20%.
[0067] (2) Methyl 4-fluorocinnamate, LiTFSI and azobisisobutyronitrile are dissolved in dimethyl sulfoxide to obtain a polymerization precursor mixture, in which the mass proportion of methyl 4-fluorocinnamate in the polymerization precursor mixture is 20%.
[0068] (3) The organic skeleton obtained in step (1) is immersed in the polymer precursor mixed solution obtained in step (2) at a temperature of 25° C. for 5 min. After immersion, the mixture is taken out and vacuum dried at a temperature of 75° C. to obtain a solid polymer electrolyte membrane. Based on the total mass of the polymer electrolyte (the mass of the solid polymer electrolyte membrane minus the mass of the organic skeleton), the mass proportion of LiTFSI is 20%. The thickness of the solid polymer electrolyte membrane is 45 μm. The mass ratio of the organic skeleton to the polymer electrolyte in the solid polymer electrolyte membrane is 2:3.
[0069] Example 2 The difference between the preparation process of the solid polymer electrolyte membrane of Example 2 and the preparation process of the solid polymer electrolyte membrane of Example 1 is as follows: In step (1), the mass proportion of p-toluenesulfonyl hydrazide in the mixed solution is adjusted to 10%, so that the porosity of the organic framework obtained in step (1) of Example 2 is 40%.
[0070] Example 3 The difference between the preparation process of the solid polymer electrolyte membrane of Example 3 and the preparation process of the solid polymer electrolyte membrane of Example 1 is as follows: In step (1), the mass proportion of p-toluenesulfonyl hydrazide in the mixed solution is adjusted to 5%, so that the porosity of the organic framework obtained in step (1) of Example 3 is 20%.
[0071] Example 4 The difference between the preparation process of the solid polymer electrolyte membrane of Example 4 and the preparation process of the solid polymer electrolyte membrane of Example 1 is as follows: In the organic framework obtained in step (1) of Example 4, the mass proportion of LiTFSI based on the total mass of the organic framework is 35%.
[0072] Example 5 The difference between the preparation process of the solid polymer electrolyte membrane of Example 5 and the preparation process of the solid polymer electrolyte membrane of Example 1 is as follows: In the organic framework obtained in step (1) of Example 5, the mass proportion of LiTFSI based on the total mass of the organic framework is 50%.
[0073] Example 6 The difference between the preparation process of the solid polymer electrolyte membrane of Example 6 and the preparation process of the solid polymer electrolyte membrane of Example 1 is as follows: The polymerization monomer used in step (2) of Example 6 is allyl 3-amino-4-fluorobenzoate.
[0074] Example 7 The difference between the preparation process of the solid polymer electrolyte membrane of Example 7 and the preparation process of the solid polymer electrolyte membrane of Example 1 is as follows: The polymerization monomer used in step (2) of Example 7 is pentafluorobenzyl methacrylate.
[0075] Example 8 The difference between the preparation process of the solid polymer electrolyte membrane of Example 8 and the preparation process of the solid polymer electrolyte membrane of Example 1 is as follows: The polymerization monomer used in step (2) of Example 8 is 2-fluorophenyl allyl ether.
[0076] Example 9 The difference between the preparation process of the solid polymer electrolyte membrane of Example 9 and the preparation process of the solid polymer electrolyte membrane of Example 1 is as follows: The polymerization monomer used in step (2) of Example 9 is ethyl α-cyano-4-fluorocinnamate.
[0077] Example 10 The difference between the preparation process of the solid polymer electrolyte membrane of Example 10 and the preparation process of the solid polymer electrolyte membrane of Example 1 is as follows: The polymerization monomer used in step (2) of Example 10 is methyl cinnamate.
[0078] Embodiment 11 The difference between the preparation process of the solid polymer electrolyte membrane of Example 11 and the preparation process of the solid polymer electrolyte membrane of Example 1 is: In step (3) of Example 11, the mass ratio of the organic skeleton to the polymer electrolyte is 3:2.
[0079] Example 12 The difference between the preparation process of the solid polymer electrolyte membrane of Example 12 and the preparation process of the solid polymer electrolyte membrane of Example 1 is: In step (3) of Example 12, the mass ratio of the organic skeleton to the polymer electrolyte is 4:1.
[0080] Embodiment 13 The difference between the preparation process of the solid polymer electrolyte membrane of Example 13 and the preparation process of the solid polymer electrolyte membrane of Example 1 is: Step (1) was replaced by dissolving polyvinylidene fluoride and LiTFSI in dimethyl sulfoxide to obtain an electrospinning precursor solution. The electrospinning high voltage was set to 15 kV and the feed rate was 1 mL h -1 , an organic skeleton precursor is obtained, which is then vacuum dried at 150°C to obtain an organic skeleton. The porosity of the organic skeleton is 60%. Based on the total mass of the organic skeleton, the mass of LiTFSI accounts for 20%.
[0081] Comparative Example 1 The difference between the preparation process of the solid polymer electrolyte membrane of Comparative Example 1 and the preparation process of the solid polymer electrolyte membrane of Example 10 is as follows: In step (1) of comparative example 1, no lithium salt was added during the preparation of the organic framework.
[0082] Comparative Example 2 The preparation process of the solid polymer electrolyte membrane of Comparative Example 2 is as follows: (1) Step (1) of Comparative Example 2 The preparation process of the organic skeleton is the same as that of Example 1.
[0083] (2) Polyacrylonitrile and LiTFSI are dissolved in dimethyl sulfoxide to obtain a mixed solution, wherein the solid content of the mixed solution is 20%.
[0084] (3) The organic skeleton obtained in step (1) is immersed in the mixed solution obtained in step (2) at a temperature of 25° C. for 5 min. After immersion, the mixture is taken out and vacuum dried at a temperature of 75° C. to obtain a solid polymer electrolyte membrane. Based on the total mass of the polymer electrolyte (the mass of the solid polymer electrolyte membrane minus the mass of the organic skeleton), the mass proportion of LiTFSI is 20%. The thickness of the solid polymer electrolyte membrane is 45 μm. The mass ratio of the organic skeleton to the polymer electrolyte in the solid polymer electrolyte membrane is 2:3.
[0085] Test example In order to verify the performance of the solid polymer electrolyte membrane provided by the present invention, the performance of the solid polymer electrolyte membrane prepared in each embodiment and comparative example was further tested. The details are as follows: (1) Ionic conductivity test method A stainless steel-solid polymer electrolyte membrane-stainless steel symmetric battery was assembled and the battery was subjected to electrochemical impedance spectroscopy with a frequency range of 0.1 Hz-1 MHz and a test amplitude of 10 mV.
[0086] (2) Cyclic performance test Assembly of solid-state batteries: 1) Positive electrode: The mass ratio of lithium nickel cobalt manganese oxide, PVDF and conductive carbon black is 8:1:1.
[0087] 2) Use lithium metal negative electrode as the negative electrode.
[0088] 3) Stack the positive electrode sheet, solid polymer electrolyte membrane and negative electrode sheet in sequence and assemble them into a solid-state battery 4) The battery was tested using the Xinwei battery performance test system with a voltage range of 2.5V-4.2V and a charge and discharge condition of 0.1C cycle at room temperature. The corresponding capacity retention rate was calculated after 100 cycles.
[0089] (3) Tensile strength test method The solid polymer electrolyte membrane was cut into strips of 8 cm × 2 cm and the tensile strength was tested using a tensile testing machine at a tensile rate of 20 mm / min.
[0090] The performance test results of the solid polymer electrolyte membranes of the embodiments and comparative examples are shown in Table 1.
[0091] Table 1
[0092] As can be seen from Table 1, the solid polymer electrolyte membrane of the present invention has excellent mechanical properties and good ionic conductivity, and the battery prepared by using the solid polymer electrolyte membrane of the present invention has excellent specific capacity and cycle performance. Comparing Example 10 with Comparative Example 1, there is no lithium salt in the organic skeleton of Comparative Example 1, and the ionic conductivity of Comparative Example 1 is significantly lower than that of Example 10. Comparing Example 1 with Comparative Example 1, the organic skeleton in Comparative Example 1 has neither lithium salt nor polymer monomers containing fluorine groups, so the ionic conductivity, mechanical properties and cycle performance of Comparative Example 1 are poor. Although Comparative Example 2 uses an organic skeleton containing lithium, the polymer electrolyte is not in situ polymerized in the organic skeleton, and the polymer used does not have fluorine groups, etc. Therefore, although the ionic conductivity of Comparative Example 2 is improved to a certain extent compared with Comparative Example 1, the mechanical properties and cycle performance are still very poor. Comparing Example 1 and Example 13, because the organic skeleton used in Example 13 is prepared by electrospinning, although the porosity of the organic skeletons of Example 1 and Example 13 is the same, there are certain differences in the pore morphology, thickness, filling rate of polymer electrolyte, and connection degree between polymer electrolyte and organic skeleton obtained by different preparation methods, which leads to differences in the performance of the solid polymer electrolyte membrane finally formed. This shows that the organic skeleton prepared by the foaming agent in the present application is easier to combine with the polymer electrolyte of the present application, thereby significantly improving the performance of the solid polymer electrolyte membrane. In summary, it is shown that the lithium salt in the organic skeleton of the present invention provides a continuous Li + Pathway and uniform Li + The flux increases the ionic conductivity of the solid polymer electrolyte membrane. The polymer electrolyte self-polymerizes in the pores of the organic skeleton to tightly connect and fully fill the skeleton voids, which significantly improves the mechanical strength of the solid polymer electrolyte membrane.
[0093] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A solid polymer electrolyte membrane, characterized in that: include: An organic skeleton, wherein the organic skeleton comprises a polymer and a lithium salt, wherein the polymer comprises at least one of a polyether, a polyester and a polyolefin; A polymer electrolyte is filled in the pores of the organic skeleton. The polymer electrolyte is formed by polymerization of a polymer monomer, a lithium salt and an initiator in the pores of the organic skeleton.
2. The solid polymer electrolyte membrane according to claim 1, characterized in that: The mass proportion of the lithium salt in the organic skeleton is 5-50%, preferably 20-50%; And / or, the porosity of the organic framework is 20-60%.
3. The solid polymer electrolyte membrane according to claim 1, characterized in that: The polyether comprises at least one of polyethylene oxide and polyethylene glycol; and / or, the polyester comprises at least one of polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, polymethyl methacrylate, polyethylene glycol methyl ether methacrylate, polycarbonate, polypropylene carbonate and polypropylene carbonate; And / or, the polyolefin includes at least one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyvinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene, polyacrylonitrile, polyethylene, polypropylene, polyvinyl chloride, polystyrene and polytetrafluoroethylene.
4. The solid polymer electrolyte membrane according to claim 1, characterized in that: The polymerizable monomer includes at least one of an ether functional group and an ester functional group, and the polymerizable monomer also includes at least one of a cyano group and a fluorine group; Preferably, the polymerizable monomer includes at least one of 3-amino-4-fluorobenzoic acid allyl ester, 4-amino-3-fluorobenzoic acid allyl ester, 4-fluorocinnamic acid ethyl ester, 4-fluorocinnamic acid methyl ester, pentafluorophenyl acrylate, pentafluorobenzyl methacrylate, pentafluorophenyl methacrylate, 2-fluorophenyl allyl ether, allyl pentafluorophenyl ether and α-cyano-4-fluorocinnamic acid ethyl ester; And / or, the mass proportion of the lithium salt in the polymer electrolyte is 5-50%, preferably 20-50%.
5. The solid polymer electrolyte membrane according to any one of claims 1 to 4, characterized in that: The mass ratio of the organic skeleton to the polymer electrolyte is (2-4): (1-3); And / or, the solid polymer electrolyte membrane has a thickness of 30 μm to 70 μm.
6. A method for preparing a solid polymer electrolyte membrane according to any one of claims 1 to 5, characterized in that: include: (1) dissolving a polymerization monomer, a lithium salt and an initiator in a solvent to obtain a polymerization precursor mixed solution; (2) The organic skeleton is immersed in the polymer precursor mixture and then dried to obtain a solid polymer electrolyte membrane.
7. The method according to claim 6, characterized in that: In step (2), the drying temperature is 60-100°C, preferably 60-80°C; And / or, the soaking time is 5-10 min and the temperature is 25°C-30°C.
8. The method according to claim 6 or 7, characterized in that: The method for preparing the organic skeleton comprises: dissolving a polymer, a lithium salt and a foaming agent in a solvent, coating and drying the solvent to obtain an organic skeleton; And / or, the drying temperature is 60-250°C, preferably 60-200°C; And / or, the foaming agent includes at least one of an azo compound, a sulfonyl hydrazide compound, a semicarbazide, a tetrazole compound, a nitroso compound and a carbonate.
9. A solid-state battery, characterized in that: The invention comprises the solid polymer electrolyte membrane described in any one of claims 1 to 5 or the solid polymer electrolyte membrane prepared by the method described in any one of claims 6 to 8.
10. A mechanical device, characterized in that: Comprising the solid-state battery as described in claim 9.
Citation Information
Patent Citations
Preparation method and application of polycarbonate-based polymer electrolyte
CN109802174A
Composite gel polymer electrolyte membrane and application thereof in lithium ion battery
CN114520366A
Polymer solid electrolyte, preparation method thereof and battery
CN118630308A
Layers for inhibiting metal dendrite growth in electrochemical cells and electrochemical cells made therefrom
CN118661282A
Manufacturing method of solid electrolyte film and electrolyte film, and lithium secondary cell using the same
JP2003017124A
Cited By
Solid-state lithium ion battery polymer electrolyte based on p-fluorocinnamic acid
CN119890437A